X-RAY SPECTRAL PROPERTIES OF THE ISOLATED AGNs: NGC 1050, NGC 2989, ESO 317-038, ESO 438-009 - Vavilova, I. B.; Vasylenko, A. A.; Babyk, Iu. V.; Pulatova, N. G. (Одеські астрономічні публікації, 2016)
We have analyzed the spectral data obtained by XMM-Newton, Swift, Chandra, and INTEGRAL space observatories for several isolated AGNs from 2MIG catalogue, for which the available X-ray data were accessed. Among these objects were CGCG 179-005, NGC 6300, NGC 1050, NGC 2989, WKK 3050, ESO 438-009, and ESO 317-038. We determined corresponding spectral models and values of their parameters (spectral index, intrinsic absorption etc.). X-ray spectra for bright galaxies, NGC 6300 and Circinus, were analyzed up to 250 keV and their characteristics of emission features were determined in 6-7 keV range. We present the results for NGC 1050, NGC 2989, ESO 317-038, and ESO 438-009, for which their spectral parameters were obtained for the first time.